Perbandingan Tingkat Efisiensi Bank Syariah Konvensional dan Unit Usaha Syariah: Pendekatan Data Envelopment Analysis - Nurfauzi Latif (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2026)
This study aims to compare the efficiency levels of Sharia Commercial Banks (BUS) and Sharia Business Units (UUS) in Indonesia using the Data Envelopment Analysis (DEA) method. The research uses secondary data from 13 BUS and 19 UUS for the 2021–2025 period, sourced from the Financial Services Authority. The results show that BUS has a significantly higher average technical efficiency score of 0.861, compared to 0.789 for UUS. This gap is primarily caused by differences in scale efficiency rather than managerial capability, as UUS faces limitations in operational autonomy and shared cost allocation with its conventional parent bank. These findings support the policy direction of separating UUS into independent entities to strengthen overall industry efficiency.